The Antimicrobial Resistance Crisis: Causes, Consequences, and Management - Michael, Carolyn Anne; Dominey-Howes, Dale; Labbate, Maurizio (Frontiers in Public Health, 2014)
The Antimicrobial Resistance (AMR) crisis is the increasing global incidence of infectious diseases affecting the human population, which are untreatable with any known antimicrobial agent. This crisis will have a devastating cost on human society as both debilitating and lethal diseases increase in frequency and scope. Three major factors determine this crisis: 1/ The increasing frequency of AMR phenotypes amongst microbes is an evolutionary response to the widespread use of antimicrobials. 2/ The large and globally connected human population allows pathogens in any environment access to all of humanity. 3/ The extensive and often unnecessary use of antimicrobials by humanity provides the strong selective pressure that is driving the evolutionary response in the microbial world. Of these factors, the size of the human population is least amenable to rapid change. In contrast the remaining two factors may be affected, so offering a means of managing the crisis: The rate at which AMR, as well as virulence factors evolve in microbial world may be slowed by reducing the applied selective pressure. This may be accomplished by radically reducing the global use of current and prospective antimicrobials. Current management measures to legislate the use of antimicrobials and to educate the healthcare world in the issues, while useful, have not comprehensively addressed the problem of achieving an overall reduction in the human use of antimicrobials. We propose that in addition to current measures and increased research into new antimicrobials and diagnostics, a comprehensive education programme will be required to change the public paradigm of antimicrobial usage from that of a first line treatment to that of a last resort when all other therapeutic options have failed.